Characterization of suppressor T cells for antibody production by chicken spleen cells. I. Antigen-induced suppressor cells are CT8+, TcR1+ (gamma delta) T cells. - Quere, P (1990)
Suppressor activity of chicken T cells has been previously defined in an in vitro assay of the secondary response of spleen cells to sheep erythrocytes. We have used this assay to examine the phenotype of the T-cell subpopulation(s) that is responsible for this activity. The suppressive effect was alleviated by removal of the TcR1+ (gamma delta) and CD8+ subpopulations, but was unaffected by the removal of the TcR2+ (alpha beta) and CD4+ cells. The addition of a histamine type 2 (H2) receptor antagonist, cimetidine, enhanced the antibody response in the presence of the suppressor cells. The data indicate that one type of T cells with suppressor capability expresses TcR1 and the CD8 accessory molecule, and that these cells may be influenced via H2 receptors.